Pengaruh Latihan Kelincahan Tehadap Kemampuan Menggiring Pemain Sepak Bola Club Leparissa Amalatu Kabupaten Seram Bagian Barat - Ukratallo, Isnan; Hasbullah, Bahmid (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2020)
Football is a game that requires technique, cohesiveness and cooperation. Mastery of basic techniques will reflect the skill level of the football player concerned. Physical skills in question are strength, speed, agility, flexibility, balance, and endurance. Agility training is very important, because what is needed when dribbling is how athletes are able to avoid themselves from opposing opponents while still controlling and maintaining the ball without losing balance, with the research location at the Alba Batu Mera club. This study uses a quantitative method with a field experiment approach with a one-grop test-post test research design. Based on the results of hypothesis testing in this study, it is known that there is an effect of agility training on the ability of the Alba Batu Merah Ambon club soccer player. This shows that agility training can have a strong influence on the ability to dribble very well so that it can be explained that agility training is an alternative that can be used to improve the ability to dribble.